Analisis Cost Volume Profit untuk Perencanaan Laba pada Restoran Praline & Oregano - Leviandi Adhie; Vinny Stefanie Sukmajaya (Cakrawala Repositori IMWI, 2020)
This study aims to determine how the analysis of cost volume profit for profit planning Praline & Oregano Restaurants. The research methodology used in this study is a descriptive study by analyzing the financial statements of Praline & Oregano Restaurants with a time span of 2Q 2017 - 1Q 2019 using cost volume profit analysis. The results found that the highest contribution margin occurred in the category Other drinks which included Dilmah, ice tea, and mineral water and Fussion Bite food categories which included Acapulco Tori, Paneer Dori With Kuah Padeh, Crispy Yakitori, and Yummy Tandoori. This study also found that the Break Even Point of Praline & Oregano restaurants in each quarter from quarter 2 2017 to quarter 2 2019 was always achieved with a nominal range of Rp. 89,211,165 - Rp. 186,159,079 this happens because the sales generated are greater than the break-even sales. This study also found that the Margin Of Safety is known to experience a fluctuating increase in the ratio of 62-76% which indicates that the company always benefits. This study calculates Praline & Oregano's profit target will get a profit of Rp. 274,925,768 in the 3rd quarter of 2019.